Efektifitas Inovasi Video Berbasis Learning dalam Meningkatkan Interaksi pada Proses Belajar Mengajar - Ramadhan, Aditama; Rinakit, Abyan Taruna; Aisy, Alya Rihhadatul; Anindita, Najla Pasya (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2025)
The innovation of learning-based instructional videos holds great potential to enhance interaction during the learning process. This study aims to evaluate the effectiveness of using learning-based videos compared to traditional teaching methods. Using a qualitative approach with classroom action research (CAR), data were collected from 91 students across two schools through questionnaires and direct observation. The findings reveal that video usage not only enhances students’ learning motivation but also fosters active engagement in class discussions. Visually and interactively presented videos assist students in understanding complex concepts, despite challenges such as technological limitations and insufficient teacher training. This study concludes that the innovation of video-based learning significantly contributes to improving teaching effectiveness and student motivation, emphasizing the need for improved technological infrastructure and teacher training to optimize technology-based learning.